Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

5.7E: Variation of Parameters (Exercises)

  • Page ID
    18321
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)

    Q5.7.1

    In Exercises 5.7.1–5.7.6 use variation of parameters to find a particular solution.

    1. \(y''+9y=\tan 3x\)

    2. \(y''+4y=\sin 2x\sec^2 2x\)

    3. \(y''-3y'+2y={4\over 1+e^{-x}}\)

    4. \(y''-2y'+2y=3e^x \sec x\)

    5. \(y''-2y'+y=14x^{3/2}e^x\)

    6. \(y''-y={4e^{-x}\over 1-e^{-2x}}\)

    Q5.7.2

    In Exercises 5.7.7-5.7.29 use variation of parameters to find a particular solution, given the solutions \(y_{1}, y_{2}\) of the complementary equation.

    7. \(x^2y''+xy'- y=2x^2+2; \quad y_1=x, \quad y_2={1\over x}\)

    8. \({xy''+(2-2x)y'+(x-2)y=e^{2x}; \quad y_1=e^x, \quad y_2={e^x\over x}}\)

    9. \(4x^2y''+(4x-8x^2)y'+(4x^2-4x-1)y=4x^{1/2}e^x, \quad x > 0\); \(y_1=x^{1/2} e^x,\; y_2=x^{-1/2}e^x\)

    10. \(y''+4xy'+(4x^2+2)y=4e^{-x(x+2)};\quad y_1=e^{-x^2}, \quad y_2=xe^{-x^2}\)

    11. \(x^2y''-4xy'+6y=x^{5/2},\, x > 0;\quad y_1=x^2,\; y_2=x^3\)

    12. \(x^2y''-3xy'+3y=2x^4\sin x; \quad y_1=x,\; y_2=x^3\)

    13. \((2x+1)y''-2y'-(2x+3)y=(2x+1)^2e^{-x}; \quad y_1=e^{-x}, \quad y_2=xe^x\)

    14. \(4xy''+2y'+y=\sin\sqrt x; \quad y_1=\cos\sqrt x, \quad y_2=\sin\sqrt x\)

    15. \(xy''-(2x+2)y'+(x+2)y=6x^3e^x;\quad y_1=e^x,\quad y_2=x^3e^x\)

    16. \(x^2y''-(2a-1)xy'+a^2y=x^{a+1}; \quad y_1=x^a, \quad y_2=x^a \ln x\)

    17. \(x^2y''-2xy'+(x^2+2)y=x^3\cos x; \quad y_1=x\cos x, \quad y_2=x\sin x\)

    18. \(xy''-y'-4x^3y=8x^5;\quad y_1=e^{x^2},\; y_2=e^{-x^2}\)

    19. \((\sin x)y''+(2\sin x-\cos x)y'+(\sin x-\cos x)y=e^{-x}; \quad y_1=e^{-x},\quad y_2=e^{-x}\cos x\)

    20. \(4x^2y''-4xy'+(3-16x^2)y=8x^{5/2}; \quad y_1=\sqrt xe^{2x},\; y_2=\sqrt xe^{-2x}\)

    21. \(4x^2y''-4xy'+(4x^2+3)y=x^{7/2}; \quad y_1=\sqrt x\sin x,\; y_2=\sqrt x\cos x\)

    22. \(x^2y''-2xy'-(x^2-2)y=3x^4;\quad y_1=xe^x,\; y_2=xe^{-x}\)

    23. \(x^2y''-2x(x+1)y' +(x^2+2x+2)y=x^3e^x; \quad y_1=xe^x, \quad y_2=x^2e^x\)

    24. \(x^2y''-xy'-3y=x^{3/2}; \quad y_1=1/x, \quad y_2=x^3\)

    25. \(x^2y''-x(x+4)y'+2(x+3)y=x^4e^x; \quad y_1=x^2, \quad y_2=x^2e^x\)

    26. \(x^2y''-2x(x+2)y'+(x^2+4x+6)y=2xe^x; \quad y_1=x^2e^x, \quad y_2=x^3e^x\)

    27. \(x^2y''-4xy'+(x^2+6)y=x^4; \quad y_1=x^2\cos x, \quad y_2=x^2\sin x\)

    28. \((x-1)y''-xy'+y=2(x-1)^2e^x; \quad y_1=x, \quad y_2=e^x\)

    29. \(4x^2y''-4x(x+1)y'+(2x+3)y=x^{5/2}e^x; \quad y_1=\sqrt x, \quad y_2=\sqrt xe^x\)

    Q5.7.3

    In Exercises 5.7.30–5.7.32 use variation of parameters to solve the initial value problem, given \(y_{1}\), \(y_{2}\) are solutions of the complementary equation.

    30. \((3x-1)y''-(3x+2)y'-(6x-8)y=(3x-1)^2e^{2x}, \quad y(0)=1,\; y'(0)=2\); \(y_1=e^{2x},\; y_2=xe^{-x}\)

    31. \((x-1)^2y''-2(x-1)y'+2y=(x-1)^2, \quad y(0)=3,\quad y'(0)=-6\);

    \(y_1=x-1\), \(y_2=x^2-1\)

    32. \((x-1)^2y''-(x^2-1)y'+(x+1)y=(x-1)^3e^x, \quad y(0)=4,\quad y'(0)=-6\);

    \(y_1=(x-1)e^x,\quad y_2=x-1\)

    Q5.7.4

    In Exercises 5.7.33-5.7.35 use variation of parameters to solve the initial value problem and graph the solution, given that \(y_{1}\), \(y_{2}\) are solutions of the complementary equation. 

    33. \({(x^2-1)y''+4xy'+2y=2x, \quad y(0)=0,\; y'(0) =-2; \quad y_1={1\over x-1},\; y_2={1\over x+1}}\)

    34. \({x^2y''+2xy'-2y=-2x^2, \quad y(1)=1,\; y'(1)= -1; \quad y_1=x,\; y_2={1\over x^2}}\)

    35. \((x+1)(2x+3)y''+2(x+2)y'-2y=(2x+3)^2, \quad y(0)=0,\quad y'(0)=0\); \(y_1=x+2,\quad y_2={1\over x+1}\)

    Q5.7.5

    36. Suppose

    \[y_p=\overline y+a_1y_1+a_2y_2\]

    is a particular solution of

    \[P_0(x)y''+P_1(x)y'+P_2(x)y=F(x), \tag{A}\]

    where \(y_1\) and \(y_2\) are solutions of the complementary equation

    \[P_0(x)y''+P_1(x)y'+P_2(x)y=0.\]

    Show that \(\overline y\) is also a solution of (A).

    37. Suppose \(p\), \(q\), and \(f\) are continuous on \((a,b)\) and let \(x_0\) be in \((a,b)\). Let \(y_1\) and \(y_2\) be the solutions of

    \[y''+p(x)y'+q(x)y=0\]

    such that

    \[y_1(x_0)=1, \quad y_1'(x_0)=0, \quad y_2(x_0)=0, \quad y_2'(x_0)=1.\]

    Use variation of parameters to show that the solution of the initial value problem

    \[y''+p(x)y'+q(x)y=f(x), \quad y(x_0)=k_0,\; y'(x_0)=k_1,\]

    is

    \[\begin{array}{rcl} y(x) &= k_0y_1(x)+k_1y_2(x) \\ & +\int^x_{x_0}\left(y_1(t)y_2(x)- y_1(x)y_2(t)\right) f(t)\exp\left(\int^t_{x_0}p(s)\,ds\right)\,dt. \end{array}\]

    HINT: Use Abel's formula for the Wronskian of \(\{ y_{1}, y_{2}\}\), and integrate \(u_{1}'\) and \(u_{2}'\) from \(x_{0}\) to \(x\).

    Show also that

    \[\begin{array}{rcl} y'(x) &= k_0y_1'(x)+k_1y_2'(x) \\ & +\int^x_{x_0}\left(y_1(t)y_2'(x)-y_1'(x)y_2(t) \right)f(t)\exp\left(\int^t_{x_0}p(s)\,ds\right)\,dt. \end{array}\]

    38. Suppose \(f\) is continuous on an open interval that contains \(x_0=0\). Use variation of parameters to find a formula for the solution of the initial value problem

    \[y''-y=f(x), \quad y(0)=k_0,\quad y'(0)=k_1.\]

    39. Suppose \(f\) is continuous on \((a,\infty)\), where \(a<0\), so \(x_0=0\) is in \((a,\infty)\).

    1. Use variation of parameters to find a formula for the solution of the initial value problem \[y''+y=f(x), \quad y(0)=k_0,\quad y'(0)=k_1.\] HINT: You will need the addition formulas for the sine and cosine. \[\begin{aligned} \sin (A+B)&=\sin A\cos B +\cos A\sin B \\ \cos (A+B) &=\cos A\cos B - \sin A\sin B \end{aligned}\] For the rest of this exercise assume that the improper integral \(\int_{0}^\infty f(t)\,dt\) is absolutely convergent.
    2. Show that if \(y\) is a solution of \[y''+y=f(x) \tag{A}\] on \((a,\infty)\), then \[\lim_{x \to \infty}\left(y(x)-A_0\cos x-A_1\sin x\right)=0 \tag{B}\] and \[\lim_{x\to\infty}\left(y'(x)+A_0\sin x-A_1\cos x\right)=0, \tag{C}\] where \[A_0=k_0-\int_0^\infty f(t)\sin t\,dt \quad \text{and} \quad A_1=k_1+\int_0^\infty f(t)\cos t\,dt.\] HINT: Recall from calculus that if \(\int _{0}^{\infty} f(t)dt\)  converges absolutely, then \(\lim_{x\to ∞}\int_{x}^{\infty}|f(t)|dt=0\).
    3. Show that if \(A_0\) and \(A_1\) are arbitrary constants, then there’s a unique solution of \(y''+y=f(x)\) on \((a,\infty)\) that satisfies (B) and (C).